Effects of Different Lipid Extractions on Gelatinization and Retrogradation of Bitter Nuts (Gnetum gnemon) Starch - Tri Agus Siswoyo (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2004)
The effect of different lipid extraction on gelatinization and retrogradation of bitter nuts (Gnetum gnemon) starch was studied by the measurement of starch-lipids complex formation using differential scanning calorimetry. The bitter nuts samples were extracted sequentially with hexane for surface lipid starch (SL) and hot water-saturated butanol for internal lipid starch (IL). The gelatinization enthalpies of starch increased significantly with extracting step, but the starch-lipid complex enthalpies of SL and IL were statistically lower, when compared with the native starch. According to the Avrami equation, the retrogradation rate of native bitter nuts starch was slower than that of the SL or IL, whereas the retrogradation rate of IL was slower than SL. High number of starch-lipids complex could retard the retrogradation of bitter nuts starch during storage. Key words : Gnetum gnemon, bitter nuts, gelatinization, retrogradation, avrami equation, starch-lipid complex.